Trafficking and effect of released DNA on cGAS-STING signaling pathway and cardiovascular disease - Zhou, Zimo; Ou-yang, Changhan; Chen, Qingjie; Ren, Zhanhong; Guo, Xiying; Lei, Min; Liu, Chao; Yang, Xiaosong (Frontiers in Immunology, 2023)
Evidence from clinical research and animal studies indicates that inflammation is an important factor in the occurrence and development of cardiovascular disease (CVD). Emerging evidence shows that nucleic acids serve as crucial pathogen-associated molecular patterns (PAMPs) or non-infectious damage-associated molecular patterns (DAMPs), are released and then recognized by pattern recognition receptors (PRRs), which activates immunological signaling pathways for host defense. Mechanistically, the released nucleic acids activate cyclic GMP-AMP synthase (cGAS) and its downstream receptor stimulator of interferon genes (STING) to promote type I interferons (IFNs) production, which play an important regulatory function during the initiation of an innate immune response to various diseases, including CVD. This pathway represents an essential defense regulatory mechanism in an organism’s innate immune system. In this review, we outline the overall profile of cGAS-STING signaling, summarize the latest findings on nucleic acid release and trafficking, and discuss their potential role in CVD. This review also sheds light on potential directions for future investigations on CVD.